The Association Between the Characteristics of Pregnant Women with Knowledge and Attitudes Toward Midwifery Care Based on Gender Sensitivity - Maryanah; Sri Sukamti; Aticeh (Window of Health : Jurnal Kesehatan, 2024)
Respectful maternity care must be ensured that all pregnant women can accept it. It is necessary to understand all pregnant women receiving midwifery care with a gender-sensitive approach to prevent the possibility of mistreatment, harassment, or violence during midwifery practice. This study aimed to assess the association between the characteristics of pregnant women and the knowledge and attitudes regarding gender-sensitive midwifery care. This was a cross-sectional study on 200 pregnant women who came to get antenatal care services at independent practice midwives. The sample was selected using a purposive sampling technique. Multivariate logistic regression analysis was performed to obtain the odds ratio, 95% confidence interval, and p-value for the trend to assess the strength of the association. Data was collected using a questionnaire that was developed and has been assessed for validity and reliability. Pregnant women who actively participate in community activities are associated with good knowledge of midwifery care with a gender sensitivity approach (OR equal 1.51, OR equal 1.16-1.97, p-value equal 0.03). Pregnant women with higher education levels are associated with a good attitude toward midwifery care with a gender sensitivity approach (OR equal 2.02, 95% CI equal 1.01-4.05, p-value equal 0.04). Pregnant women participating in community activities are associated with good knowledge about midwifery care with a gender sensitivity approach, and pregnant women with higher education levels are associated with good attitudes about midwifery care with a gender sensitivity approach (p-value less than 0.001). Midwives and other health workers educate pregnant women in all health facilities at every antenatal visit and community activities such as the village community health center.